In vitro maturation in synthetic oviductal fluid increases gene expression associated with quality and lipid metabolism in bovine oocytes - Mendes, Adriano Felipe; Puelker, Raquel Zaneti [UNESP]; De Souza, Lilian Francisco Arantes; Jacintho, Andréa Renesto Coimbra; Dos Santos, Priscila Helena [UNESP]; Giometti, Ines Cristina; Firetti, Sheila Merlo; De Souza Castilho, Anthony César [UNESP]; Zundt, Marilice; Membrive, Claudia Maria Bertan [UNESP]; Castilho, Caliê (Cambridge University Press (CUP), 2023)
Traditionally, in vitro oocyte and embryo culture progresses through a series of varying culture medium. To investigate simplifying the in vitro production of bovine cumulus-oocyte complexes (COCs), this study used synthetic oviductal fluid (SOF) supplemented with conjugated linoleic acid (CLA). Special interest was placed on gene expression linked to lipid metabolism and oocyte maturation. COCs were matured in different media: Medium 199 (M199 group), M199 with 100 μMCLA (M199 + CLA group), SOF (SOF group), and SOF with 100 μMCLA (SOF + CLA group). COCs matured with SOF showed a higher relative abundance of mRNA of quality indicators gremlin 1 (GREM1) and prostaglandin-endoperoxide synthase 2 (PTGS2) in oocytes, and GREM1 in cumulus cells compared with in the M199 group. SOF medium COCs had a higher relative abundance of fatty acid desaturase 2 (FADS2) compared with the M199 group, which is essential for lipid metabolism in oocytes. Furthermore, the abundance of stearoyl-coenzyme A desaturase 1 (SCD1) in oocytes matured with SOF was not influenced by the addition of CLA, whereas the relative abundance of SCD1 was reduced in M199 medium with CLA. We concluded that maturation in SOF medium results in a greater abundance of genes linked to quality and lipidic metabolism in oocytes, regardless of the addition of CLA.
Keywords: Conjugated linoleic acid; Cumulus-oocyte complexes; IVF; Lipid metabolism; Synthetic oviductal fluid